Transformıng Mathematıcs Learnıng Through An Intensıve Program: A Quantıtatıve Analysıs In Elementary Students - Jusmida; Yustitia , Via (Jurnal Elementaria Edukasia, 2024)
This study examines the effectiveness of an intensive learning program in improving elementary students’ mathematics achievement. The research was motivated by persistent difficulties among Indonesian students in mastering basic numeracy, as highlighted by national and international assessments. Using a quantitative pre-experimental one-group pretest–posttest design, the study involved 30 third-grade students at SD Negeri 33 Waimnir during the second semester of the 2023/2024 academic year. The intervention was delivered over six weeks (12 sessions, 90 minutes each) through active learning, structured practice, small-group discussion, and immediate teacher feedback. Learning outcomes were measured with a content-valid test instrument reviewed by two mathematics education experts and an experienced teacher; reliability testing using the split-half method produced a coefficient of 0.87, indicating high reliability. Data analysis comprised descriptive statistics, Shapiro–Wilk tests for normality, and a paired-samples t-test. The mean score increased from 55.03 (SD = 9.58) on the pre-test to 69.17 (SD = 7.80) on the post-test, yielding a mean difference of 14.13 points. Normality assumptions were met (Shapiro–Wilk p = 0.094 and p = 0.128), and the paired-samples t-test showed a statistically significant improvement (t(29) = −12.34, p < .001). The findings indicate that an intensive, well-structured program with focused exercises and active teacher guidance can substantially enhance students’ numeracy competencies. Practical implications include the adoption and scaling of intensive sessions tailored to learners’ needs to transform mathematics learning toward deeper conceptual mastery.